2016
DOI: 10.1186/s12862-016-0587-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persisting hybrid swarm and geographic difference in hybridization pattern: genetic consequences of secondary contact between two Vincetoxicum species (Apocynaceae–Asclepiadoideae)

Abstract: BackgroundDuring glacial periods, glacial advances caused temperate plant extirpation or retreat into localized warmer areas, and subsequent postglacial glacial retreats resulted in range expansions, which facilitated secondary contact of previously allopatric isolated lineages. The evolutionary outcomes of secondary contact, including hybrid zones, dynamic hybrid swarm, and resultant hybrid speciation, depends on the strengths of reproductive barriers that have arisen through epistatic and pleiotropic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…) breakdown of postmating barriers, with evidence of temporal stability in several cases (e.g., Li et al. ). Intraspecific lineage fusion is particularly likely when environmental heterogeneity between lineages is minimal (Seehausen ; Seehausen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) breakdown of postmating barriers, with evidence of temporal stability in several cases (e.g., Li et al. ). Intraspecific lineage fusion is particularly likely when environmental heterogeneity between lineages is minimal (Seehausen ; Seehausen et al.…”
Section: Discussionmentioning
confidence: 99%
“…), often with evidence that lineages are temporally stable (e.g., Li et al. ). Regardless of whether early‐generation hybrids have reduced fertility or reproductive success, subsequent generations can still form a stable lineage (Arnold et al.…”
mentioning
confidence: 99%
“…These studies have demonstrated that information from pheromone-based trapping during a single field season generally can surpass the known information about most rare species several times over, and that existing records often provide an underestimation of their true distributions. Pheromones also have been used for systematic DNA sampling for phylogeographic studies of E. ferrugineus (Oleksa et al 2015) and the Spanish moon moth G. isabellae (Mari-Mena et al 2016). In parallel with monitoring for conservation purposes, monitoring systems with pheromones and other semiochemicals support the detection of invasive pest species at low densities (Liebhold et al 2016), including monitoring their range expansion (Liebhold and Bascompte 2003; Suckling et al 2014), and the effectiveness of eradication efforts (Kean and Suckling 2005; Kikkert et al 2006; Lance and Gates 1994).…”
Section: Estimating Change: Distributions and Population Sizesmentioning
confidence: 99%
“…Pheromones have been used sporadically by collectors and conservationists in their search for rare and cryptic species, for example by using live females to attract males (Mari-Mena et al 2016), or by utilizing single synthetic pheromone components or partial pheromone blends (Buda et al 1993). During the last 10–15 years, however, increasing attention has been directed towards exploiting the powerful attraction of insect pheromones as monitoring tools in biodiversity and conservation research.…”
Section: Introductionmentioning
confidence: 99%
“…These two scenarios are not always mutually exclusive: for example, ancient hybridization might be followed by rapid diversification which in turn leads to extensive hybridization among the resulting species. During the formation of a syngameon, the interacting species essentially form a single gene pool due to high levels of gene flow and can be seen as hybrid swarms (Arnold, 1997, Li et al, 2016b, Wiens et al, 2006.…”
Section: The Syngameon Scenariomentioning
confidence: 99%